Caregivers Burden of Patients with Schizophrenia and Bipolar Disorder: A Sectional Study - Vasudeva, S. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Caregiving has been identified as a basic component of human nature and a primary element of close relationship. This study aims to assess the extent and pattern of burden felt by the caregivers of patients with schizophrenia in comparison with bipolar disorder. MATERIALS AND METHODS: Fifty-two patients with schizophrenia and fifty-one patients with bipolar disorder attending the outpatient department were assessed in the study. The burden among the caregivers was assessed using Burden Assessment Schedule. RESULTS: The caregivers of schizophrenia group had significantly higher total burden score as compared to caregivers of bipolar disorder. Caregivers of schizophrenia experienced significantly higher burden in area of external support, caregivers routine, and other relations. CONCLUSION: The extent of burden among families of schizophrenic patients is more than those of bipolar disorder. The families of patients with bipolar disorder do also experience considerable burden. The pattern of burden among families of schizophrenia and bipolar disorder is almost identical in most of the domains except for external support, caregivers routine, and other relations.